Diabetes-Mediated Toxicity Resulted in the Expression of CD80 and CD86 on Neutrophils after Delayed Wound Healing in Male Rats. (14th July 2020) - Ebaid, Hossam; Abdel-Salam, Bahaa; Hassan, Iftekhar; Al-Tamimi, Jameel; Metwalli, Alli; Rady, Ahmed; Alhazza, Ibrahim M.
Abstract : Background . Polymorphonuclear neutrophils (PMNs) play an essential role in the innate immune response, and their number increases after prolonged inflammatory diabetic wounds and prolonged wounds in older rats. The expression of CD80 and CD86 on PMNs confirms their participation in acquired immunity, wherein these molecules are involved in antigen presentation. Materials and Methods . We investigated CD80 and CD86 expression on PMNs by flow cytometry and analyzed the mRNA expression of neutrophil chemoattractants macrophage inflammatory protein-2 ( MIP-2 ) and MIP-1α by real-time polymerase chain reaction (PCR) in diabetic wound, which was healed by a camel milk peptide (CMP). The animals were allocated to the following wounded groups: control, diabetic (DM), and diabetic treated with CMP (DM-CMP). Results . Alkaline phosphatase, gamma-glutamyl transpeptidase, and lactate dehydrogenase levels were elevated in DM rats but decreased in peptide-treated rats. The expression of CD80 and CD86 was significantly higher in DM rats with prolonged wounds than in control rats. The expression of both markers was restored to normal levels in diabetic rats treated with CMP. RT-PCR analysis revealed the upregulation in MIP-2 mRNA expression in DM rats. However, neutrophil number at wounded sites of DM rats declined at day 1 after wounding as compared to that in control rats. MIP-2 mRNA expression and neutrophil number were restored in CMP-treated diabetic rats. Conclusion . Prolonged wound stress induced toxicity in DM rats and significantly increased the expression of CD80 and CD86 on PMNs. CMP peptide ameliorated the levels of toxicity markers, CD80 and CD86, and chemoattractant molecules in diabetic rats.